ANALISIS SARANA DAN PRASARANA DI SEKOLAH MENENGAH ATAS ISLAM TERPADU (SMA IT) DAARUSSALAAM SUKABUMI - Miftahudin, Ujang; Erihadiana, Mohamad; Jahari, Jaja; Syaf , Solehudin (Prodi Manajemen Pendidikan Islam, 2023)
This paper aims to determine the condition of the facilities and infrastructure in Daarussalaam Integrated Islamic Senior High School (SMA IT) and make a simple comparison between the actual conditions in the field with the minimum standards of facilities and infrastructure contained in Permendiknas No. 24 of 2007 concerning Standards of Facilities and Markets for Primary and Secondary Education Units. The comparisons include: 1) classrooms, 2) library rooms, 3) biology laboratory rooms, 4) physics laboratory rooms, 5) chemistry laboratory rooms, 6) computer laboratory rooms, 7) language laboratory rooms, 8) leadership rooms, 9) teacher room, 10) administration room, 11) place of worship, 12) counseling room, 13) UKS room, 14) student organization room, 15) latrine, 16) warehouse, 17) circulation room and 18) playground / exercising. The data obtained by the author is data from field observations at SMA IT Daarussalaam on November 22, 2020. The method used by the author is field observation techniques and informal and non-formal interviews with the school. From the results obtained by the authors in this study it can be concluded that 12 of the 18 categories of minimum facility standard fulfillment in Permendiknas No. 24 of 2007 has been fulfilled, although there are several facilities that are not fulfilled by the school such as: chemistry, physics, and biology laboratories, this is because SMA IT Daarussalaam is a school with a new category, namely in 2020. Therefore, currently it only has one department, namely the language department.